Malignancies in people living with HIV: A 25-years observational study from a tertiary hospital in Italy - Antonio Anastasia; Walter Mazzucco; Luca Pipitò; Santo Fruscione; Roberta Gaudiano; Marcello Trizzino; Maurizio Zarcone; Antonio Cascio (Journal of Infection and Public Health)
Background: HIV infection has been associated with an increased risk of cancer development and Kaposi’s sarcoma, non-Hodgkin’s lymphoma, and invasive cervical cancers have been a manifestation of AIDS. With the advent of antiretroviral therapy, a collateral appearance of non-AIDS defining cancers (NADC) has been observed in HIV positive patients. Methods: From January 1997 to December 2022, we performed an observational cross-sectional study, involving HIV-infected outpatients with both AIDS-defining cancers (ADC) and NADC, followed up in a tertiary hospital in Italy. Results: Overall, 153 cases of malignancy were observed, with a higher percentage of NADC (60.8 %) rather than ADC (39.2 %). Mean age at tumour diagnosis was significantly lower for ADC than for NADC in HIV positive individuals (p-value= 0.001). No statistical difference was found between the mean values of zenith HIV-RNA and CD4 count in HIV outpatients with cancer and in those without cancer, while a statistically significant difference was found between the HIV-RNA zenith in HIV outpatients with ADC as compared with NADC (10.2 copies/mL versus 8.1 copies/mL; p-value= 0.007). Conclusions: Our study revealed a considerably high proportion of non-AIDS defining malignancies in HIV individuals, emphasizing the need to improve the management of these cancer patients at follow up according to the risk profiles and the changing epidemiology.